Effects of Acacia mearnsii supplementation on nutrition, parasitological, blood parameters and methane emissions in Santa Ines sheep infected with Trichostrongylus colubriformis and Haemonchus contortus - Tavares Lima, Paulo de Mello; Crouzoulon, Pierre; Sanches, Tamires Pinheiro; Zabre, Genevieve; Kabore, Adama; Niderkorn, Vincent; Hoste, Herve; Talamini do Amarante, Alessandro Francisco [UNESP]; Costa-Junior, Livio Martins; Abdalla, Adibe Luiz; Louvandini, Helder (Elsevier B.V., 2019)
Gastrointestinal nematodes are a main problem for ruminant production, reducing animal performance and increasing environmental impact per unit of animal product generated. Tannin supplementation may lead to positive results regarding aspects such as parasitic infections and methane (CH4) emissions. Therefore, the objective of this experiment was to evaluate the effects of the condensed tannins (CT) extract made of powdered Acacia mearnsii bark (PAB) on nutrition, parasitic status and CH4 emissions in sheep artificially infected with Trichostrongylus colubriformis and Haemonchus contortus. Twenty 10-month old Santa Ines lambs (24.7 +/- 3.14 kg of initial body weight) were used in a 50-day trial. Animals were divided in four treatment groups according to parasitic infection and PAB supplementation: two control groups without infections, one without PAB (C-) (n = 4) and one with PAB (C+) (n = 4); two infected groups, one without PAB (I-) (n = 6) and another receiving PAR (I+) (n = 6). Initially, animals were kept in individual pens where they were fed ad libitum chopped tifton 85 hay (Cynodon spp.) and 210 g/animal/day of concentrate. On the first day of experiment, animals of I- and I+ groups were artificially infected with infective larvae (L3) of T. colubriformis and H. contortus. Lambs were weighed fortnightly to calculate average daily body weight gain (ADG). Blood and faeces samples were also collected in the same moment of weighing for the evaluation of blood parameters and faecal egg count (FEC) respectively. After 40 days of experiment, measurements of CH4 emissions in small chamber system started and following that, apparent total tract digestibility (ATTD) assay was carried out in metabolic cages. In the end of experimental period (50 days), lambs were slaughtered and samples of abomasum and small intestine content were collected for worm count, identification, and eggs/female count. No significant (p > 0.05) treatment effects were verified for ADG, ATTD and worm count. Blood parameters were affected in both infected groups (p < 0.05) from the 28th experimental day onwards, when these animals started to show reduced red blood cells, haemoglobin and packed cell volume when compared to C- and C+. Decreased FEC was verified in I+ when compared to I- and also, H. contortus eggs/female worm for I+ was lower than for I- (p < 0.05). Both infected groups showed higher CH4 emissions than the control groups (p < 0.05). Results highlighted the anthelmintic potential of PAR and indicated methanogenic effect of parasitic nematode infections.
Keywords: Black wattle; Greenhouse gases; Nematodes; Small ruminants; Sustainability; Tannins